Haunted Memories : Portraits of Women in the Holocaust - Eichengreen, Lucille 1925-2020 (PublishingWorks, 2011)
Numerous memoirs have helped shed light on the horrors of Nazi Germany, but none have offered the heartbreaking sincerity and careful consideration of women's experiences that Lucille Eichengreen's Haunted Memories: Portraits of Women in the Holocaust details. Eichengreen offers a thorough and heartfelt look at the female experience of the Nazi camps. Telling the tale of her own survival, Eichengreen's work explores all the women she encountered, from the empowered female SS guards to the prisoners who were forced to trade sex for food. With unwaveringly straightforward prose, Eichengreen isn'